Computer Aided Distributed Post-Stroke Rehabilitation Environment - Wrzeszcz, Michał; Otfinowski, Janusz; Słota, Renata; Kitowski, Jacek (Computer Science, 2016)
In this paper we present the results of a two-year study aimed at developing a full-fledged computer environment supporting post-stroke rehabilitation. The system was designed by a team of computer scientists, psychologists and physiotherapists. It adopts a holistic approach to rehabilitation. In order to extend the rehabilitation process, the applied methods include a remote rehabilitation stage which can be carried out of at the patient’s home. The paper presents a distributed system architecture as well as results achieved by patients prior to and following a three-month therapy based on the presented system.